Penerapan Kurikulum Merdeka Belajar di Sekolah Penggerak Kabupaten Agam - Wahyuni, Yulia Septi (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This research aims to find out how the Merdeka Belajar curriculum management is implemented in Driving Schools at the Primary School level in Agam Regency, and also to find out what factors influence the implementation of the Independent Learning curriculum management in Driving Schools at the Primary School level in Agam Regency, West Sumatra. Data collection techniques were carried out using interviews, observations and documents. The method used in this research is descriptive qualitative. Data is analyzed by reviewing the data, organizing the data, dividing it into manageable units, synthesizing to look for patterns, finding what is meaningful from what is researched and reporting systematically. The results of the research show that firstly, in general, Baso District Elementary School has implemented an independent curriculum as determined by the government, namely conducting learning in accordance with the curriculum structure in the independent curriculum, and has also carried out comprehensive assessments. Second, the factors or variables that influence the implementation of independent curriculum management in driving schools in Baso District Public Elementary Schools are the principal, teachers, and school learning facilities.